Islamic Philantrophy as a Mechanism to Improve Agricultural Products and Sustenance in Refugees Camps in the Sub-Region of Lake Chad Basin - Muhammad Auwal Sulaiman (UIN Sunan Gunung Djati Bandung, 2023)
Insecurity of crossing Lake Chad Basin and Northeast Nigeria has seriously affected activities of farming, fishing, and other agricultural programs in the region. The lake provides water for irrigation, fishing activities, water for cattle, and water transportation across four counties that share the lake. The paper has discovered that many communities have abandoned their agricultural activities and relocated to IDPs for their safety of life. As a result, the affected communities increasingly suffer from great loss, unemployment, and poverty. Using the descriptive and analytical method, this study discussed the socioeconomic role of Islamic philanthropy in funding the agricultural sector to restore sources of livelihood of the refugee camps in Northeast Nigeria. Philanthropy, known as waqf, is a voluntary charity in terms of land and property. Moreover, philanthropy is a strong instrument to reduce various burdens of life. Meanwhile, this study recommends a design to reach the targeted communities.